Virtual electrode effects in myocardial fibers. - Knisley, S B (1994)
The changes in transmembrane potential during a stimulation pulse in the heart are not known. We have used transmembrane potential sensitive dye fluorescence to measure changes in transmembrane potential along fibers in an anisotropic arterially perfused rabbit epicardial layer. Cathodal or anodal extracellular point stimulation produced changes in transmembrane potential within 60 microns of the electrode that were positive or negative, respectively. The changes in transmembrane potential did not simply decrease to zero with increasing distance, as would occur with a theoretical fiber space constant, but instead became reversed beyond approximately 1 mm from the electrode consistent with a virtual electrode effect. Even stimulation from a line of terminals perpendicular to the fibers produced negative changes in transmembrane potential for cathodal stimulation with the largest negative changes during a 50-ms pulse at 3-4 mm from the electrode terminals. Negative changes as large as the amplitude of the action potential rising phase occurred during a 50-ms pulse for 20-volt cathodal stimulation. Switching to anodal stimulation reversed the directions of changes in transmembrane potential at most recording spots, however for stimulation during the refractory period negative changes in transmembrane potential were significantly larger than positive changes in transmembrane potential. Anodal stimulation during diastole with 3-ms pulses produced excitation in the region of depolarization that accelerated when the stimulation strength was increased to > 3 times the anodal threshold strength. Thus, virtual electrode effects of unipolar stimulation occur in myocardial fibers, and for sufficiently strong stimuli the virtual electrode effects may influence electrical behavior of the myocardium.